Development of Tools for Forwarding Somersault Skills - Gunawan, Sani; Millah, Haikal; Mulyana, Fegie Rizkia (Journal of Physical Education and Sports, 2018)
The study that has been carried out aims to develop specific learning aids for floor gymnastic forward somersault skills. Other objectives of this study are to be used as a material for study in class discussions, seminars and other discussion forums specifically for studying the problems of learning and training methods for floor gymnastics. The fundamental thing that underlies this research is to enrich science through research in the field of teaching especially floor gymnastics teaching for forwarding somersault skills. This is a practical way to improve student learning outcomes through developing media or forward somersault learning tools. In this study, the aspects taken are learning media, namely the development of a tool or a tool that is useful for facilitating the learning process on floor gymnastics courses. The method in this study uses research and development (R & D) developed by Sukmadinata. This research is expected to produce early products that will be tested for effectiveness in the following year as well as the emergence of appropriate efforts in providing floor gymnastics teaching with the use of tools specifically for forward somersault skills.